A Regenerative Approach to Canine Osteoarthritis Using Allogeneic, Adipose-Derived Mesenchymal Stem Cells. Safety Results of a Long-Term Follow-Up - Kriston-Pál, Éva; Haracska, Lajos; Cooper, Paul; Kiss-Tóth, Endre; Szukacsov, Valéria; Monostori, Éva (Frontiers in Veterinary Science, 2020)
Mesenchymal stem cells (MSC) are emerging as an effective therapeutic tool in treating canine osteoarthritis (OA). However, long-term follow-up reports on the safety of MSC transplantation are still missing. In this study, we focused on the question of whether MSC transplantation is associated with an increased incidence of other diseases or adverse reactions. Allogeneic MSCs were used to treat canine OA. Visceral adipose tissue, a surgical waste obtained during routine ovariectomy served as a source of MSCs. Altogether, fifty-eight dogs were transplanted in the study, and divided into two groups, depending on the site of OA: Elbow (42 animals) and amalgamated hip, knee, ankle, and hock (16 animals, ‘other joint’). The effect of MSC transplantation was evaluated by the degree of lameness at a 4-5-year follow-up period based on the owners’ subjective observations. The results showed that 83% of both the elbow and ‘other joint’ OA patients improved or retained improvement. Clinical safety of the treatment was assessed by evaluating the coincidence of tumours or other diseases, as well as other adverse reactions (such as local inflammation) with MSC cell therapy. Two incidences of local inflammation for less than one week at the site of injection were reported. No other adverse reactions were detected post-treatment. Sixteen dogs died during the study, 4 due to cancer and 12 due to other diseases. Overall, no enrichment in a specific cause of death was observed in the transplanted animals. Our data suggests that MSC treatment is a safe long-term therapy for canine OA.